ANALISIS MUTU HEDONIK ABON IKAN PATIN (Pangasius sp.) DENGAN PENAMBAHAN JANTUNG PISANG KEPOK (Musa paradisiaca L) - Febriana, Nisrina; Junianto, Junianto; Maulina, Ine; Rostini, Iis (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
The objective of processing catfish into shredded products is to increase consumption patterns and expand the marketing reach. To improve product quality, diversification, competitiveness, quality and efficiency, innovation is required. The addition of fibre to shredded catfish can enhance product quality while maintaining cost-effectiveness. The alternative fibre source used was kepok banana blossom, which has the potential to enhance the organoleptic characteristics of the product. The study implemented a completely randomised design with four treatment levels of banana heart addition (22.5%, 25%, 27.5%) with 20 replicates. The hedonic test include appearance, aroma, flavour, and texture. The optimal treatment was the addition of 25% banana heart, which achieved an appearance value of 6.9, aroma 6.9, flavour 7, and texture 6.7.